Assessment of Phytoremediation Potential of Chara vulgaris to Treat Toxic Pollutants of Textile Effluent - Pooja Mahajan; Jyotsna Kaushal; Arun Upmanyu; Jasdev Bhatti (Journal of Toxicology)
Textile effluent released into water bodies is prone to be toxic for aquatic flora and fauna. In the present study, the phytoremediation potential of Chara vulgaris (C. vulgaris) is investigated for treatment of textile effluent. The highly concentrated and toxic textile effluent is diluted to different concentrations 10%, 25%, 50%, and 75% to check the accessibility of macroalgae to bear pollutant load of textile effluent. The toxicity of textile effluent is analysed by determining different water quality parameters, namely, pH, TDS, BOD, COD, and EC. The maximum reductions in TDS (68%), COD (78%), BOD (82%), and EC (86%) were found in the 10% concentrated textile effluent after 120 h of treatment. The highly concentrated textile effluent showed its toxic effect on macroalgae and it was found unable to show a remarkable change in water quality parameters of 75% and 100% textile effluent. The correlation coefficient values are determined using correlation matrix to identify the high correlation between different water quality parameters. The removal of toxic organic pollutants by C. vulgaris was confirmed by using UV-visible absorption spectra. Typical X-ray spectra recorded using EDXRF technique indicated the presence of heavy metals Cd in the dried sample of macroalgae after treatment which show its capability to remove toxic heavy metals from textile effluent. The reliability model has been proposed for treated textile effluents to identify percentage level of toxicity tolerance of waste water by macroalgae.